The reform of the confraternities of New Spain in the Council of the Indies, 1767-1820 - Carbajal López, David (Revista Complutense de Historia de América, 2012)
The Council of the Indies participated actively in the reform of the confraternities of New Spain, through the review of more than a hundred specific expedients between 1767 and 1820. Through its fiscales, the Council tried to extend the Crown’s jurisdiction over the religious brotherhoods, displacing the clergy and redefining the institutions as “bodies of laymen”. But the reform also contemplated the reduction of expenses associated with worship, for the benefit of charity, and the elimination of all forms of obligation, compensation or “profane vanity”, in favour of the disinterstedness and self-will of what they also called “pious congregations”. The fiscales sought to reinforce their religious character and their role in protecting the sacred.
Keywords: Confraternities; Religious Brotherhoods; Bourbon Reforms; Worship; Charity; Piety; Mexico; 18th Century.